Impact of mild hypothermic circulatory arrest on surgical outcomes in acute type a aortic dissection patients: a single-centre study - Zhenxiong Li; Hao Tang; Chao Deng; Kangjun Shen; Jingyu Li; Song Tian; WenYao Zhan; Ling Tan (BMC Cardiovascular Disorders)
Abstract Background As hypothermic circulatory arrest (HCA) is being more frequently induced in patients undergoing aortic arch surgery, its safety at different degrees has become a crucial area of study. The aim of this study was to assess the surgical outcomes of mild hypothermic circulatory arrest (MI-HCA) during aortic arch surgery. Methods Acute type A aortic dissection (ATAAD) patients who underwent total arch replacement (TAR) and frozen elephant trunk (FET) surgery between January 2014 and December 2023 were enrolled in this study. The patients were divided into two groups according to the minimum nasopharyngeal temperature: the moderate hypothermic circulatory arrest (MHCA) group (20–28 °C) and the MI-HCA group (> 28 °C). The inverse probability of treatment weighting (IPTW) was used to balance differences in the baseline characteristics. Perioperative variables were analysed via pairwise comparisons, multivariable logistic regression, and subgroup forest plots to assess the impact of MI-HCA on surgical outcomes. Results A total of 447 patients were included in this study, and the mean minimum nasopharyngeal temperature was 24.80 (23.98, 27.30) °C in the MHCA group and 30.10 (29.80, 30.70) °C in the MI-HCA group. The incidence of acute kidney injury (AKI) in the MI-HCA group was lower than that in the MHCA group (52% vs. 78%, p < 0.01). In the multivariable logistic regression analysis, MI-HCA was identified as an independent protective factor for AKI (OR = 0.354, 95% CI 0.177–0.689; p = 0.003). Additionally, compared with MHCA, MI-HCA was not associated with an increased incidence of stroke, spinal cord injury, or in-hospital mortality. After IPTW, the preoperative and intraoperative data of the patients were balanced, and the incidence of AKI in the MI-HCA group was still lower than that in the MHCA group (83.26% vs. 53.61%, p = 0.004). The subgroup forest plot also demonstrated that MI-HCA was a protective factor for postoperative AKI. Conclusions The surgical outcomes of MI-HCA in ATAAD patients were satisfactory. Compared with MHCA, MI-HCA provided sufficient protection for distal organs, the brain, and the spinal cord, with a significantly lower incidence of AKI. These results indicate that MI-HCA could be a better approach for ATAAD surgery.